In vitro and in vivo analyses of co-infections with peste des petits ruminants and capripox vaccine strains - Zhang, Dajun (Virol J, 2021)
BACKGROUND: Peste des petits ruminants (PPR) and goat pox (GTP) are two devastating animal epidemic diseases that affect small ruminants. Vaccination is one of the most important measures to prevent and control these two severe infectious diseases. METHODS: In this study, we vaccinated sheep with PPR and POX vaccines to compare the changes in the antibody levels between animals vaccinated with PPRV and POX vaccines alone and those co-infected with both vaccines simultaneously. The cell infection model was used to explore the interference mechanism between the vaccines in vitro. The antibody levels were detected with the commercial ELISA kit. The Real-time Quantitative PCR fluorescent quantitative PCR method was employed to detect the viral load changes and cytokines expression after the infection. RESULTS: The concurrent immunization of GTP and PPR vaccine enhanced the PPR vaccine's immune effect but inhibited the immune effect of the GTP vaccine. After the infection, GTP and PPR vaccine strains caused cytopathic effect; co-infection with GTP and PPR vaccine strains inhibited the replication of PPR vaccine strains; co-infection with GTP and PPR vaccine strains enhanced the replication of GTP vaccine strains. Moreover, virus mixed infection enhanced the mRNA expressions of TNF-α, IL-1β, IL-6, IL-10, IFN-α, and IFN-β by 2–170 times. GTP vaccine strains infection alone can enhanced the mRNA expression of IL-1β, TNF-α, IL-6, IL-10, while the expression of IFN-α mRNA is inhibited. PPR vaccine strains alone can enhanced the mRNA expression of IFN-α, IFN-β, TNF-α, and has little effect the mRNA expression of IL-1β, IL-6 and IL-10. The results showed that GTP and PPR vaccine used simultaneously in sheep enhanced the PPR vaccine's immune effect but inhibited the immune effect of the GTP vaccine in vivo. Furthermore, an infection of GTP and PPR vaccine strains caused significant cell lesions in vitro; co-infection with GTP + PPR vaccine strains inhibited the replication of PPR vaccine strains, while the co-infection of GTP followed by PPR infection enhanced the replication of GTP vaccine strains. Moreover, virus infection enhanced the expressions of TNF-α, IL-1β, IL-6, IL-10, IFN-α, and IFN-β. CONCLUSIONS: Peste des petits ruminants and capripox vaccine strains interfere with each other in vivo and vitro.